Surrogate constraint normalization rules for a capital budgeting model - Paixão, J.P; Costa, A. (EURO-INFORMS 2013, 2013)
We report on the application of surrogate relaxation approaches for a linear integer program related to a capital budgeting problem. We derive and computationally test several of rules for initializing and updating the constraint weights associated to the surrogating process. The computational experience is carried out for a set of test instances previously considered in the literature.